THE INDIGENOUS GROUPS AND THE BRAZILIAN SWEETS - Mártin César Tempass (Espaço Ameríndio, 2008)
In the books of Gilberto Freyre and Câmara Cascudo, that influencied so much the literature about brazilian alimentation, the participation of indigenous groups in the national sweets formation process is negligencied. However, is possible to find in book´s “interlineations” of these two authors valuables informations about indigenous contributions to this process. Starting from these two authors and based in the culinary system notion, this paper quests to situate the role of indigenous groups in the brazilian sweets formation and numbers the possibles causes to invisibility of sweets by indigenous at the culinary formation process.